A multiscale model for the numerical simulation of the anchor bolt pull-out test in lightweight aggregate concrete. (1st October 2015) - Greco, Fabrizio; Leonetti, Lorenzo; Luciano, Raimondo
Highlights: A concurrent multiscale approach is used for studying fracture phenomena in LWAC. An ad-hoc path following method is proposed to simulate crack propagation in LWAC. The competition between different damage mechanisms in LWAC is considered. The overall nonlinear response of LWAC for anchor bolt pull-out tests is obtained. The influence of aggregates' quality and content on LWAC's response is studied. Abstract: Lightweight aggregate concrete (LWAC) has been increasingly used as a construction material in civil and building engineering, especially in earthquake hazard zones, due to its higher strength-to-weight ratio and efficient handling with respect to ordinary concrete. The aim of the present work is to perform complete failure analyses in LWAC taking into account the effects of the underlying microstructure on its overall structural behavior. To this end, a concurrent multiscale method is adopted, in conjunction with an innovative crack modeling framework. Continuous crack propagation along a non-prescribed path is modeled in the LEFM setting, taking advantage of a shape optimization method coupling a moving mesh strategy and a gradient-free optimization solver. The crack penetration through a material interface is also taken into account, by means of a novel re-initiation criterion at interface, based on a material characteristic length. Numerical computations have been carried out with reference to the complete failure analysis of a LWAC specimen subjected to the anchor bolt pull-out test; the related results have shown that the peak and post-peak response is strongly affected by volume fraction and Young's modulus of lightweight aggregates. Their validation has been performed by means of comparisons with a fully homogenized model uniquely based on LEFM approach.